EVALUASI PROGRAM PEMUDA PELOPOR DI DINDIKPORA KABUPATEN REMBANG - Arfanisa Fadia Firdausi; Ari Subowo; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Indonesia is facing the challenge of the 2020-2035 demographic bonus. It is important for youth to take part in every aspect of public activities to develop a pioneering spirit. The pioneer youth program is one of the government's programs to appreciate young people who have played a role, made new breakthroughs, were able to create real works that the community could feel their impact, and pioneered other youths to play a role in regional progress. The purpose of this study was to determine the evaluation of the implementation of the pioneer youth program in Rembang Regency, analyze the driving and inhibiting factors, and determine the role of pioneer youth in the development of Rembang Regency. The study uses the Stufflebeam model program evaluation theory (CIPP), which sees the important purpose of an evaluation as improving, not proving something. This research is descriptive qualitative by taking a case study at the Department of Education, Youth, and Sports in Rembang Regency. Data collection techniques were carried out by interviewing, library research and documentation through primary and secondary data sources. The results show that the pioneer youth program in Rembang Regency has been running well, it's just that the socialization system that is carried out is still lacking and limited so that it has an impact on the low number of participants in this program. So in this study it can be concluded that the low participation of youth in participating in the pioneer youth program is caused by the socialization system that is still less effective, the institution should be able to take full advantage of social media platforms and media partners and send letters directly to each agency so that information can be obtained. related to this program can be spread widely